2018
DOI: 10.1111/pce.13428
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin produced by maize flavone synthase I and II protects plants against UV‐B‐induced damage

Abstract: Flavones, one of the largest groups of flavonoids, have beneficial effects on human health and are considered of high nutritional value. Previously, we demonstrated that maize type I flavone synthase (ZmFNSI) is one of the enzymes responsible for the synthesis of O-glycosyl flavones in floral tissues. However, in related species such as rice and sorghum, type II FNS enzymes also contribute to flavone biosynthesis. In this work, we provide evidence that maize has both one FNSI and one FNSII flavone synthases. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 95 publications
(161 reference statements)
1
38
0
Order By: Relevance
“…Previous studies have reported that maysin and rhamnosylisoorientin, two UV-absorbing flavones, accumulate in maize leaves of high-altitude lines in response to UV-B radiation [11]. Overexpression of either the maize FNS enzyme (ZmFNSI and ZmFNSII) in Arabidopsis was shown to decrease UV-B induced damage [12]. Additionally, accumulation of apigenin 5-O-glucoside in rice enhanced its tolerance to UV radiation [35].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have reported that maysin and rhamnosylisoorientin, two UV-absorbing flavones, accumulate in maize leaves of high-altitude lines in response to UV-B radiation [11]. Overexpression of either the maize FNS enzyme (ZmFNSI and ZmFNSII) in Arabidopsis was shown to decrease UV-B induced damage [12]. Additionally, accumulation of apigenin 5-O-glucoside in rice enhanced its tolerance to UV radiation [35].…”
Section: Discussionmentioning
confidence: 97%
“…The continuous thinning of the atmospheric ozone layer in recent years has caused an increase in damage to plants by solar UV radiation. Several studies have shown that the content of flavones is higher in the leaves of plants growing at high altitudes than in those of plants growing at low altitudes, demonstrating a correlation between flavones and plant tolerance to UV stress [11,12]. Other significant properties of certain flavones are their nutritional value and bioactivities in humans, including antioxidant and putative anticancer activity [1,13].…”
Section: Introductionmentioning
confidence: 99%
“…Various flavonoids and pigment-containing extracts have been shown to protect DNA from damage. For example, apigenin protects plants against damage induced by ultraviolet (UV)-B radiation [5]; Chinese bayberry extract protects against oxidative DNA damage [6]; grape-seed extract prevents oxidation-induced DNA damage [7]; and cyanidin-3-glucoside, along with its aglycon, protect against calf thymus DNA (ctDNA) damage [8].…”
Section: Introductionmentioning
confidence: 99%
“…There are also other genes like FNS and IFS could catalyze the flavone and isoflavone biosynthesis [14,15]. Furthermore, the transcriptional factors regulating the biosynthesis were identified in many species.…”
Section: Introductionmentioning
confidence: 99%